Leptorinth - Shakeeb Arsalaan Bajunid, Siti Farhana Bajunid; Azman, Amira Fathini; Norman, Ashreen; Gomes, Gorakanage Ashen Indimal; Zulkifli, Mohd Amirul Faiz; Md. Zuri, Izyan Fartini; Azmilumur, Muhammad Anuarruddin; Amin Nordin, Syafinaz; Saad, Wan Zuhainis (Centre for Global Open Access Learning, Immersive Technology & Quality Assurance, Universiti Sains Islam Malaysia, 2017)
Young learners have impressionable minds and are curious by nature, which allows the cultivation of a younger generation of future learners who are exposed to endless possibilities. Learning with games encourages an increase in student engagement and the information transfer becomes easier. Leptorinth integrates AR into its gameplay which allows the players to learn of the devastating effects of leptospirosis. During the process of playing the game, they become independent, thus encouraging their kinaesthetic learning with the aid of augmented reality (AR). Public awareness of such diseases where a game is involved, interests and encourages the community to learn with delight.